Suitability study of soybeans husk ash as a mixing material to OPC: Effect of calcination time-preliminary investigation - Taku, K. J.; Amartey, Y. D. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Soybeans husk was collected from a dump site, dried de-carbonated, separated into six samples and calcined at a temperature of 600 °C, for 1, 2, 3, 4, 5 and 6 hours respectively. Samples were taken for X- ray Florescence (XRF) analysis, Standard Electron Microscopy (SEM) imaging, setting time, standard water of consistency determination and specific gravity test. The result of XRF analysis revealed that the SHA contain less than 70 % SiO2+Al2O3+Fe2O3 stipulated by ASTM C618 for pozzolanas, but has very high CaO content. The SiO2 +Al2O3+Fe2O3 and CaO content though varies slightly with the calcination time of soybean husk. The specific gravity of SHA varies with calcination time of SH and ranges between 2.3 and 2.7 and is less than that of OPC irrespective of the calcination time. Setting times of OPC/SHA pastes at 10 % replacement of OPC with SHA increases with calcination time and is greater than that for OPC paste. The SEM analysis shows that the crystal structure of the SHA changes with calcination temperature. The compressive strength of mortar using OPC/SHA as a binder was determined after 7, 14 and 28 days curing and was found to be less than that for OPC mortars at all ages. However, the percentage reduction in strength decreased with curing age, with SHA calcined at 4 hours having the greater strength (i.e. 87.4 % of OPC strength at 28 days). The percentage gain in strength was more pronounced from 7 to 14 days. In all, SH calcined at 600 °C for 4 hours optimizes the pozzolanic potential of SHA. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. I, June, 2016, Page: 13-22